2020
DOI: 10.1039/d0cp00149j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid improvements in charge carrier mobility at ionic liquid/pentacene single crystal interfaces by self-cleaning

Abstract: The field-effect mobility increases with time for a few hours because of the spontaneous dissolution of the defect sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The high spatial resolution and wide environmental adaptability of AFM make this technique highly advantageous for operando characterization of OMIECs. Spatial resolution at the molecular level has been reported for structural characterization at the liquid/solid interface . In situ AFM has also been applied on polyelectrolytes to study the swelling in water vapor and the relaxation process in aqueous solutions .…”
Section: Scanning Probe Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The high spatial resolution and wide environmental adaptability of AFM make this technique highly advantageous for operando characterization of OMIECs. Spatial resolution at the molecular level has been reported for structural characterization at the liquid/solid interface . In situ AFM has also been applied on polyelectrolytes to study the swelling in water vapor and the relaxation process in aqueous solutions .…”
Section: Scanning Probe Techniquesmentioning
confidence: 99%
“…Spatial resolution at the molecular level has been reported for structural character-ization at the liquid/solid interface. 404 In situ AFM has also been applied on polyelectrolytes to study the swelling in water vapor 405 and the relaxation process in aqueous solutions. 406 In addition, the interfacial morphology changes during electrochemical polymerization of EDOT has been observed by in situ AFM.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…It should be noted here that these spectral changes were not due to the dissolution of the organic semiconductor molecule into the IL. While other organic semiconductors such as rubrene were easily dissolved into ILs 14 , the DNBST-based OFETs were stable in ILs.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…IL-gated EDL-OFETs were first reported by Takeya’s group in 2008 using rubrene single crystals 9 . This field of study has since expanded to include other organic semiconductors, such as octathio[8]circulene 10 , [7]phenacene 11 , pentacene 12 14 , and fullerene 13 . The IL species is one of several important factors determining the carrier mobility ( μ ) of a device 15 17 .…”
Section: Introductionmentioning
confidence: 99%
“…As electronic devices are composed of multiple materials and layers, their performance and functions strongly depend on not only the individual components but also the constituent interfaces. Ionic liquids (ILs) are frequently incorporated in devices, such as solar cells, light-emitting diodes, and field-effect transistors (FETs), and it has been reported that the semiconductor–IL interface plays a crucial role in protecting against oxygen- and moisture-adsorption-induced degradation, optimizing the morphology and energy levels of semiconducting layers and accumulating a high density of carriers in interfacial semiconducting layers. Accordingly, the characterization of the interfacial structures and electronic states at the atomic and/or molecular levels to clarify the relationship between the interfacial properties and device performances and, thereby, improve the device performance is paramount.…”
Section: Introductionmentioning
confidence: 99%